Baitouweng decoction modulates gut microbial production of indole-3-propionic acid and epithelial necroptosis to alleviate DSS-induced colitis in mice - Jingyi Hu; Hongxin Chen; Lei Zhu; Yiheng Tong; Cheng Cheng; Guoying Yan; Hong Shen (Chinese Medicine)
Abstract Background Ulcerative colitis (UC) is a kind of inflammatory disorder structuring in the colon. Baitouweng decoction (BD) derived from Treatise on Cold Damage (Shang-Han-Lun in Chinese) has been used for the treatment of UC in clinical practice for more than 2000 years. However, the clear mechanism of BD is still unknown. Our previous study revealed the regulation of BD on gut microbiota in colitis mice. This study aimed to investigate the crosstalk between intestinal flora and host immunity in the therapeutic effect of BD on colitis. Methods The model of colitis in mice was established using dextran sulfate sodium in drinking water, and the treatment group received BD, 5-ASA, or indole-3-propionic acid (IPA). The disease symptoms were documented, and assessments were conducted on both local and systemic inflammation as well as intestinal barrier function. The gut microbiota structure was analyzed using 16S ribosomal RNA sequencing. The metabolomic assay was performed using ultra-high performance liquid chromatography and quadrupole time-of-flight mass spectrometry, and RNA-sequencing was used to explore the mechanism of IPA on colitis treatment. Results BD could improve colitis mice’s colonic injury and rebalance the gut microbiota dysbiosis. Fecal microbiota transplantation experiments confirmed that the therapeutic effects of BD depend on the intestinal flora, while antibiotic treatment abrogated the effect of BD. The concentration of IPA, a microbial tryptophan metabolite, was upregulated after BD-treated. IPA was further evaluated for its effect on the development of colitis and it was identified as an inhibitor of necroptosis of intestinal epithelial cells. Conclusions Our findings suggest that BD could alleviate colitis by regulating the gut microbiota-metabolism homeostasis to inhibit the necroptosis of intestinal epithelial cells.